2014
DOI: 10.1590/1809-2950/37321022014
|View full text |Cite
|
Sign up to set email alerts
|

Ratings of perceived exertion at anaerobic threshold in patients with coronary artery disease

Abstract: The study aimed to identify and compare the ratings of perceived exertion (RPE) at the ventilatory anaerobic threshold (VAT) in healthy subjects and patients with coronary artery disease (CAD). A total of 30 male subjects took part in the study and were divided into three groups: a control group (CG) composed of 10 healthy participants; a group composed of 10 participants diagnosed with CAD beta-blocker user (G-DACb); and a group composed of 10 participants with CAD non-beta-blocker user (G-DAC). The participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…A study by Scherr et al 28 comparing graded exercise RPE values of coronary artery disease (CAD) patients (n=146, mean age 66 years, BMI 26.7 and 2 hours of weekly exercise) with non-cardiac participants (n=2560), using the Borg 6–20 scale, 19 showed CAD patients significantly under-rated RPE at blood lactate values of 3.0 and 4.0 mmoL/L compared with non-cardiac controls (3 mmoL/L: CAD, 12.0±1.7 vs total cohort, 13.0±1.9 RPE, p<0.001; 4 mmoL/L: CAD, 14.0±1.7 vs total cohort, 14.2±1.9 RPE, p<0.01). Forti 29 also found male CAD patients (mean age 56 years, n=10, taking beta-blockers, and n=10, not taking beta-blockers) to report significantly lower RPE values (Borg CR 10 scale) 30 during cycle ergometry compared with n=10 non-cardiac patients (RPE: 4.9, 5.9 and 6.5, respectively). Additionally, Joo et al 31 reported there is to be substantial intersubjective variability from n=11 cardiac patients (of mix condition and gender taking beta-blockers) during overground walking at RPE 11–13 19 from the 6–20 scale in relation to predetermined % V O 2 reserve ( V O 2 R).…”
Section: Discussionmentioning
confidence: 90%
“…A study by Scherr et al 28 comparing graded exercise RPE values of coronary artery disease (CAD) patients (n=146, mean age 66 years, BMI 26.7 and 2 hours of weekly exercise) with non-cardiac participants (n=2560), using the Borg 6–20 scale, 19 showed CAD patients significantly under-rated RPE at blood lactate values of 3.0 and 4.0 mmoL/L compared with non-cardiac controls (3 mmoL/L: CAD, 12.0±1.7 vs total cohort, 13.0±1.9 RPE, p<0.001; 4 mmoL/L: CAD, 14.0±1.7 vs total cohort, 14.2±1.9 RPE, p<0.01). Forti 29 also found male CAD patients (mean age 56 years, n=10, taking beta-blockers, and n=10, not taking beta-blockers) to report significantly lower RPE values (Borg CR 10 scale) 30 during cycle ergometry compared with n=10 non-cardiac patients (RPE: 4.9, 5.9 and 6.5, respectively). Additionally, Joo et al 31 reported there is to be substantial intersubjective variability from n=11 cardiac patients (of mix condition and gender taking beta-blockers) during overground walking at RPE 11–13 19 from the 6–20 scale in relation to predetermined % V O 2 reserve ( V O 2 R).…”
Section: Discussionmentioning
confidence: 90%
“…However, it has been shown that groups with different characteristics (e.g., male and female, active and sedentary, etc.) have similar RPE values at certain times of the exercise such as VAT and exercise peak [9][10][11] . The authors reported that the fact that RPE at VAT does not vary among individuals with different characteristics enables its use as complementary tool for physical exercise prescription.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, some authors have proposed the Borg CR-10 scale as a complementary tool to determine the workload related to VAT [9][10][11] . In addition, RPE has been used to prescribe exercise intensity, especially during non-supervised exercises, as it increases the accuracy and assertiveness in keeping the prescribed exercise intensity 6,11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other hand no differences were noticed in women in physical activity level in Borg´s scale, both groups showed AnT closed to level 5 in Borg´s 10 points scale (Zamunér et al, 2011). In coronary artery disease patients show 5-6 values in ventilator anaerobic threshold determination, and results may be explained by their physical condition (Forti, Zamunér, Kunz, Salviati, Nery, & Silva, 2014) In heart failure patients the exercise guided by the Borg scale maintains the patient's HR between the anaerobic threshold in the exercise training zone important parameter in this populations (Carvalho, Bocchi, & Guimarães, 2009) and its use its recommended in physicians, physical therapist and medical staff for determining the intensity of resistance exercise in clinical practice (Mahler & Rostan, 1990; Morishita, Yamauchi, Fujisawa, & Domen, 2014)…”
Section: Using Perceived Exertion To Determine Anaerobic Thresholdmentioning
confidence: 99%